Acquaintance, approach and application of pharmacovigilance: questionnaire based study at a tertiary care teaching hospital in Dhaka - Nasir, Morshed; Zahan, Tahmina; Farha, Nadia; Chowdhury, A. S. M Salauddin (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Pharmacovigilance is proven as an effective monitoring mechanism for safety and efficacy of pharmaceutical products with the assistance of physicians, pharmacists, nurses, and other healthcare professionals to avoid undue physical, mental and financial suffering of patients. Thus, this study was conducted to assess awareness of pharmacovigilance among the healthcare service providers to evaluate the acquaintance, approach application (3A) of judicial reporting of ADRs and pharmacovigilance in a tertiary care teaching hospital in Dhaka. Methods: A pre-tested questionnaire-based study was done among the 5th year medical students, interns, doctors and nurses of Holy Family Red Crescent Medical College, Dhaka, Bangladesh to assess the overall status of acquaintance (knowledge), approach (attitude) and application (practice) pharmacovigilance. Total 417 questionnaires were distributed and 389 were included as valid, compiled and analysed using SPSS version 25.0. Results: Among the respondents, almost 78% of the nurses responded the right answers and doctors responded the lowest 29% on average. The average percentage of approach and application of pharmacovigilance was low in all the respondent groups. The poorest outcome was observed about reporting an adverse drug reactions (ADR) form by all respondents as 01% to 08%. Conclusions: The overall status of pharmacovigilance in a tertiary teaching hospital was found paradoxically low, that revealed the necessity of much more initiatives at the undergraduate and postgraduate academic curriculum and intensive motivation, training, monitoring should be addressed to ensure the safety of medication, rationality of drug use and accomplish the national pharmacovigilance programs.